(untitled) (Advancements in Homeopathic Research, 2022)
In corona virus disease 2019 (COVID 19) pandemic we have no available directory, we are learning as we are progressing, with each passing day. Homeopathy has earned considerable attention in recent times, with a large number of patients getting and following homeopathic medicines for both the treatment and prevention of their complaints. Homoeopathy is well suited for use in non urban and remote sections where framework, resources and drugs needed for modern medicine is not available. The preventive aspect of Homoeopathy is well known, and historically, Homoeopathy has reportedly been used for prevention during the epidemics of Cholera, Spanish Influenza, Yellow fever, Scarlet fever, Diphtheria, Typhoid etc. As important determinants of viral infections lie within the host, homeopathy can offer vast scope of treatment. In present paper author presents her views regarding homoeopathic approach in treatment of COVID-19 patients. COVID 19 pandemic has put the health care system under great strain. If integrated approach using homeopathy is employed, it has potential to prevent hospitalization and reduce complications of the disease.